Reframing qualitative research ethics - Busby, Helen (Emerald Publishing Limited, 2025)
This book contains three chapters. Reframing Qualitative Research Ethics explores contemporary challenges in qualitative research ethics and generates proposals for reforming ethics review based on researchers' experience on the ground to support innovative qualitative research in the future. Following an introduction informed by the historical trajectory of research ethics, this volume explores some of the ethical concerns that researchers have encountered during fieldwork for their research, considers how both they and their ethics committees framed ethical issues, describes how these were managed, and reflects on what we can learn from their experiences. Granular case-studies with a focus on innovative methodologies are offered alongside reflections that go beyond the well-rehearsed binaries of oppositional debates about research ethics review. Researchers with extensive experience of research ethics review make some broader proposals for change. These include a proposal for discipline-based research ethics review, a call to broaden out ethical issues to encompass wider frameworks of research integrity, and an agenda for organisations to better support ethics and integrity in qualitative research. A timely return to the nuances of researchers' experience on the ground featuring contributors who are uniquely well-placed to bridge the divide that is commonly seen between researchers and the views of research ethics committees, this is a pathbreaking resource for a new generation of qualitative researchers and members of the research ethics community.
Keywords: Qualitative research -- Moral and ethical aspects.; Social Science -- Research.; Research and information: general.; Social research and statistics.; elektronické knihy; electronic books